2017
DOI: 10.5312/wjo.v8.i2.170
|View full text |Cite
|
Sign up to set email alerts
|

Lower limb intracast pressures generated by different types of immobilisation casts

Abstract: AIMTo determine if complete, split casts and backslabs [plaster of Paris (POP) and fiberglass] generate different intracast pressures and pain.METHODSIncreased swelling within casts was modeled by a closed water system attached to an expandable bag placed directly under different types of casts applied to a healthy lower limb. Complete fiberglass and POP casts, split casts and backslabs were applied. Twenty-five milliliter aliquots of saline were injected into the system and the generated intracast pressures w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…The pressure applied by an orthopedic cast should be minimized (under 30 mmHg) to prevent the constriction of blood flow. [ 32 ] Other thermoplastic casts have been shown to exert mean pressures of 31 ± 3 mmHg without occluding the microcirculation of the skin. [ 33 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pressure applied by an orthopedic cast should be minimized (under 30 mmHg) to prevent the constriction of blood flow. [ 32 ] Other thermoplastic casts have been shown to exert mean pressures of 31 ± 3 mmHg without occluding the microcirculation of the skin. [ 33 ]…”
Section: Resultsmentioning
confidence: 99%
“…The pressure applied by an orthopedic cast should be minimized (under 30 mmHg) to prevent the constriction of blood flow. [32] Other thermoplastic casts have been shown to exert mean pressures of 31 ± 3 mmHg without occluding the microcirculation of the skin. [33] In our experiments, the pressure was measured as a function of time using a capacitive sensing sleeve worn on the wrist of the subject underneath the cast, containing two co-facially arranged electrodes of conductive silver fabric heat-bonded to the opposite sides of the red spacer knit (Figure 1c), which served as the compressible dielectric layer for the capacitive sensing mechanism.…”
Section: Pressural Safetymentioning
confidence: 99%
“…4 In particular, tightly applied dressings can increase the patient’s perception of pain especially in the acute setting secondary to swelling. 3 A study that analyzed patients who presented to the emergency department secondary to cast concerns concluded that 23% of visits were due to tight casts and another 10% were due to pain. 6 Furthermore, anecdotally in the senior author’s upper extremity practice, patients will sometimes complain of pain associated with tight splint dressings.…”
Section: Discussionmentioning
confidence: 99%
“…The implication is that the pain may be secondary to increased below-dressing pressure between the dressing and the patient's skin. 3 In the extreme circumstance, an especially rigid or noncompliant circumferential dressing will not accommodate severe swelling, resulting in skin necrosis or even limb-threatening compartment syndrome. 4 One method to reduce the below-dressing pressure under circumferential dressings is to split the dressing longitudinally.…”
Section: Introductionmentioning
confidence: 99%
“…Garfin et al, on the other hand, discovered that univalve splitting decreased cast pressure by 65%, whereas bivalve splitting reduced cast pressure by 47% and 33% in the anterior and posterior compartments, respectively [8]. The lower limb intercast pressures measured in backslab, full POP, split POP, fibreglass and split fibreglass were 47.05 ± 31.8, 72.28 ± 60.3, 17.15 ± 7.53, 82.73 ± 67.0 and 26.58 ± 21.33 mmHg, respectively [9]. In another study, Marson and Keenan found that POP and fibreglass had mean casting pressures of 61.10 and 30.35 mmHg respectively, thus, fibreglass casting produces significantly higher pressure than POP casts [10].…”
Section: Introductionmentioning
confidence: 97%